Accountability for Mosque Financial Management: How Important Is It? - Setiawan, Nanang (Islamic Micro Finance Journal, 2024)
This study aims to explore the urgency of mosque financial management to increase financial accountability and prevent fraud. This study is a literature review using the results of previous studies. Mosque financial management is important to increase financial accountability. The scope of mosque financial management consists of financial planning, fundraising, fund management, financial reporting, internal control, and financial analysis. The potential for mosque funds is very large from zakat, infaq, shodaqoh, waqf, and funds from the government. Therefore, financial management is an urgent thing to do as a form of accountability to all stakeholders, especially Allah Ta'ala. Financial management, financial accountability, and transparency, as well as good internal control, are carried out to prevent potential fraud that can harm the organization and to maintain public trust. This study contributes to increasing literacy about mosque finance in the community and utilizing the results of mosque financial research needed by mosque administrators as well as in efforts to prevent fraud.